Polsko-amerykańskie stosunki gospodarcze w świetle inwestycji bezpośrednich w polskich strefach ekonomicznych - Mrówka, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Economic relations between Poland and the United States of America, in spite of considerably rapid development in the last decade, are still insufficient taking into account the economic possibilities of both countries. Therefore, the need for increasing the presence of the Polish economy exists in the commercial and economic turnover from the USA and also dynamics and sizes of American direct investments in Poland. This publication is an attempt to assess the commercial co-operation between both countries and to analyze US foreign direct investments in the Polish enterprise zones. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 337-347